(untitled) (Contemporary Mathematics, 2025)
On an Almost Distributive Lattice (ADL), the concept of demi-complementation is introduced. From demi-complemented ADLs, we derived some important and interesting properties. Every demi-complemented ADL is given set equivalent conditions that yields a pseudo-complemented ADL, an MS-ADL, and a pseudo-complemented lattice.